Finger Tip Replantation Tamai Zone II – A Case Report - Shrestha, Niresh; Batajoo, Santosh; Jaiswal, Sweta; Shrestha, Om Prasad (Nepal Orthopaedic Association Journal, 2023)
Fingertip injury is one of the most commonly encountered injuries in the emergency department. In our country, hand injuries can happen for various reasons, and motorbike chain injuries are the commonest. In this case report, we present a complete traumatic amputation of the right index finger at the distal interphalangeal joint caused by a motorbike chain injury. This index finger injury falls under the category of a crush avulsion. The nerve was not repaired, but the digital artery and vein were repaired during reattachment. The patient expressed satisfaction with the surgical results three months after the procedure, both in terms of functionality and appearance. This case report aims to present a successful reimplantation of the index finger without nerve repair.